Espiritualidade como suporte social no envelhecimento - Garcia, Leatrice da Luz (2019)
Aging brings its limitations and losses that tend to accentuate with advancing age. It is at this time that many older people turn to spirituality and social support, seeing them as an ally to meet the challenges of this stage of life. Therefore, the purpose of this study is to understand the role of spirituality as social support in aging, which will be presented in three articles. The first consists of an integrative literature review, which aimed to analyze whether spirituality is used as support or social support by the elderly, performed in the databases Lilacs, Medline and BDENF, from January to April 2018. It was found that spirituality was not pointed directly as social support, but, taking into account its dimensions, it can be seen that it may become an integral part of the Social Support of the elderly, as it ensures this feeling of being and belonging, reducing isolation, stimulating social ties and reinforcing the meaning of life. The second article was intended to characterize the eldery regarding sociodemographic aspects, as well as to understand the role of spirituality as social support in aging. This study happened with the application of the Spiritual Welfare Scale and the Brazil Old Age Schedule Questionnaire. The analysis of the data revealed that spirituality is important and is present in all dimensions of life of the researched elderly, influencing their well-being, the construction of their values and beliefs and their social relations. The third article sought to understand if spirituality is part of the Social Support of the elderly. Data were collected through semistructured interviews and manually analyzed using Bardin's content analysis technique. It was evident in the results that spirituality is used as a coping strategy, enabling the development of positive feelings, being seen as a motivation to overcome the adversities coming from the aging process, favoring social life.